Pelatihan Penyusunan Jurnal Penyesuaian Sebagai Upaya Penguatan Pemahaman Siklus Akuntansi Pada Siswa SMA Wiyata Dharma - Mutia Riska Faridani; Sovia Lolita Apriani Pardede; Rifdah Riyan Dara; Ripka Seriidahnaita Ginting; Esty Pudyastuti; Arif Rahman (Cattleya Darmaya Fortuna, 2026)
This community service activity was conducted at Universitas IBBI as part of the campus tour program attended by students of SMA Wiyata Dharma. One of the academic enrichment sessions in the campus tour was training on preparing adjusting entries to strengthen students' understanding of the accounting cycle. The problem addressed in this activity was the limited practical understanding of students in identifying end-of-period adjustments, determining debit and credit accounts, and linking adjusting entries to financial statement preparation. The method consisted of a short lecture, guided demonstration, case-based practice, and interactive discussion using service-company transaction examples. The activity showed that contextual and practice-oriented training helped students understand the role of adjusting entries in producing more accurate accounting information. This activity indicates that campus tour programs can be developed not only as institutional introduction activities but also as meaningful academic engagement to improve accounting literacy among senior high school students.